2020
DOI: 10.3390/antiox9020141
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivation of Carbonyl-Detoxifying Enzymes by H2O2 Is a Trigger to Increase Carbonyl Load for Initiating Programmed Cell Death in Plants

Abstract: H2O2-induced programmed cell death (PCD) of tobacco Bright Yellow-2 (BY-2) cells is mediated by reactive carbonyl species (RCS), degradation products of lipid peroxides, which activate caspase-3-like protease (C3LP). Here, we investigated the mechanism of RCS accumulation in the H2O2-induced PCD of BY-2 cells. The following biochemical changes were observed in 10-min response to a lethal dose (1.0 mM) of H2O2, but they did not occur in a sublethal dose (0.5 mM) of H2O2. (1) The C3LP activity was increased twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Wong et al proposed two major types of protein carbonylation, primary protein carbonylation and secondary protein carbonylation, to reflect how the modification occurs [ 92 ] ( Figure 3 ). Primary protein carbonylation involves metal-catalyzed oxidation (MCO) of the side chains of Lys, Pro, and Thr residues, leading to aldehyde or ketone formation [ 93 , 94 ]. Primary protein carbonylation may also occur, although to a much lesser extent, through α-amidation pathways or glutamyl side chains, which leads to the synthesis of peptides with the α-keto derivative at the N-terminal [ 13 , 95 ].…”
Section: Details Of Protein Carbonylationmentioning
confidence: 99%
“…Wong et al proposed two major types of protein carbonylation, primary protein carbonylation and secondary protein carbonylation, to reflect how the modification occurs [ 92 ] ( Figure 3 ). Primary protein carbonylation involves metal-catalyzed oxidation (MCO) of the side chains of Lys, Pro, and Thr residues, leading to aldehyde or ketone formation [ 93 , 94 ]. Primary protein carbonylation may also occur, although to a much lesser extent, through α-amidation pathways or glutamyl side chains, which leads to the synthesis of peptides with the α-keto derivative at the N-terminal [ 13 , 95 ].…”
Section: Details Of Protein Carbonylationmentioning
confidence: 99%
“…Another vicious circle has been highlighted between RCS and H2O2 (Biswas et al, 2020). RCS can alter protein function by covalent modification (Colzani et al, 2013), and H2O2 scavenging enzymes (catalase and ascorbate peroxidase) were observed in a study as targets of RCS (Mano et al, 2014).…”
Section: From Rcs To Pcdmentioning
confidence: 99%
“…In addition, an animal catalase has been shown to form adducts with HNE, leading to inactivation of the enzyme and a compromised H2O2 scavenging (Bauer and Zarkovic, 2015;Biswas et al, 2020).…”
Section: From Rcs To Pcdmentioning
confidence: 99%
“…Another interesting feature of this special issue focuses on investigating the other H 2 O 2 targets involved in programmed cell death. Dr. Mano’s group [ 8 ] studied the mechanism that increased the reactive carbonyl species in the H 2 O 2 -produced programmed cell death in tobacco Bright Yellow-2 cells. They suggested that H 2 O 2 initially inactivates a carbonyl reductase(s), which increases the reactive carbonyl species content, leading to the activation of the caspase-3-like protease of the 20S proteasome.…”
mentioning
confidence: 99%